Informativeness and Moore's Paradox - Pagin, Peter (Analysis (Oxford), 2008)
It is argued that a) non-intentional systems can exhibit what is intuitively reconizable as Moorean absurdity; b) that main-stream accounts of Moore's paradox cannot explain this; c) that an alternative account focused on informativeness (or information-giving) can explain it; d) that an account of assertoric force as prima facie informativeness is plausible; e) that the informativeness account of Moorean absurdity can explain standard examples of Moore's paradox in virtue of this theory of assertion.